The Relationship Between Pregnant Women’s Attitudes and Their Compliance in Consuming Iron (Fe) Tablets During Pregnancy in the Working Area of Syamtalira Bayu Public Health Center, North Aceh Regency - Hafsah Usman; Ernita; Marduati; Nurul Huda (International Journal of Health Engineering and Technology, 2025)
This study aims to determine the relationship between pregnant women’s attitudes and their compliance in consuming iron (Fe) tablets during pregnancy at the Syamtalira Bayu Health Center, North Aceh Regency. The research employed a quantitative cross-sectional approach with a sample of 85 pregnant women selected through purposive sampling based on the Slovin formula. Data collection was carried out by distributing questionnaires to pregnant women in their first, second, and third trimesters. The results showed that 27.1% of respondents had a positive attitude and were compliant in consuming Fe tablets, while 72.9% had a negative attitude and were non-compliant. Bivariate analysis revealed a significant relationship between attitude and compliance (p-value = 0.012, p < 0.05). These findings indicate that a positive attitude strongly influences compliance with Fe tablet consumption. Therefore, health education provided by healthcare workers should not only focus on knowledge but also aim to foster positive attitudes and commitment among pregnant women to maintain their health and that of their fetus.